Communication technologies for smart grid applications: A survey. (October 2016) - Emmanuel, Michael; Rayudu, Ramesh
Abstract: Modernization of the conventional power system is being driven by increased load, aging infrastructure and proposed legislation to increase taxation of greenhouse gas emissions. The evolving intelligent energy value chain known as the smart grid is an intricate system, which requires deliberate collaboration from various stakeholders. The smart grid is not a monolithic system but rather a collection of enabling technologies and applications with different Quality of Service (QoS) requirements. It is pivotal to any nation's economic advancement, global relevance and overall quality of life. In this article, a review of integral components of the emerging grid and communication infrastructures enabling the six smart grid applications is presented. In addition, this paper summarizes their communication and networking requirements such as payload (size and frequency), physical (PHY) and media access control (MAC) layer latency based on IEEE Guide for Smart Grid Interoperability and National Institute of Standards and Technology frameworks. Also, this article highlights the need for convergence into a common protocol platform to achieve interoperability of legacy and evolving communication protocols. Additionally, challenges of communication infrastructures deployed within the "unfriendly" power system environment and critical skill gaps that exist between the power and communication domains, which may create a 'silo unit' while integrating communication technologies into the legacy power system are presented.